Equity and access in charter schools: Identifying issues and solutions - Marshall, David T. (Education Policy Analysis Archives, 2017)
School choice exists in American public schooling, even where official school choice policy is absent. Parents with means can elect to live in neighborhoods zoned for desirable schools, whereas parents without means are locked out of that opportunity. In their ideal, charter schools have the ability to expand access to desirable schools to families who previously had little choice in their children’s schools. However, issues of equity and access often limit options for the very families who are seeking them. This paper examines four such issues in charter schools—school diversity, access to transportation, application processes, and access to quality teachers as equity and access. The issues are problematized and case studies that have worked towards resolving these issues are examined.